Probing interneuronal cell communication via optogenetic stimulation. Issue 3 (3rd June 2021) - Heeger, Patrick; Harre, Jennifer; Warnecke, Athanasia; Mueller, Dominik; Kalies, Stefan; Heisterkamp, Alexander
Abstract: This study uses an all‐optical approach to probe interneuronal communication between spiral ganglion neurons (SGNs) and neurons of other functional units, in this case cortex neurons (CNs) and hippocampus neurons (HNs), for the first time. We combined a channelrhodopsin variant (CheRiff) with a red genetically encoded calcium indicator (jRCaMP1a), enabling simultaneous optical stimulation and recording from spatially separated small neuronal populations. Stimulation of SGNs was possible with both optogenetic manipulated HNs and CNs, respectively. Furthermore, a dependency on the pulse duration of the stimulating light in regard to the evoked calcium response in the SGNs was also observed. Our results pave the way to enable innovative technologies based on "biohybrid" systems utilizing the functional interaction between different biological (eg, neural) systems. This can enable improved treatment of neurological and sensorineural disorders such as hearing loss. Abstract : This study uses an all‐optical approach to probe interneuronal communication between spiral ganglion neurons (SGNs) and neurons of other functional units, in this case cortex neurons (CNs) and hippocampus neurons (HNs), for the first time. We combined a channelrhodopsin variant (CheRiff) with a red genetically encoded calcium indicator (jRCaMP1a), enabling simultaneous optical stimulation and recording from spatially separated small neuronal populations. Our results pave the way to enable innovative technologies based on "biohybrid" systems utilizing the functional interaction between different biological (eg, neural) systems.